Regional distribution of discrimination forms in the labor market in Romania - Dobre Mihaela Hrisanta; Ailenei Dorel; Cristescu Amalia (European Regional Science Association (ERSA), 2011)
A highly segmented labor market usually favors a mismatch between supply and demand, significantly limiting the functional flexibility and the resilience of this market to macroeconomic shocks. From this perspective, such a market hampers the transition of an EU member to the euro zone, adversely affecting the quality of integration. The causes of labor market segmentation are related to: imperfect competition between firms, information asymmetry, how workers signal on the labor market, limited mobility of workers across different sectors, etc. Labor market segmentation can be done according to several criteria: type of employment, length of employment, salary level, gender, ethnicity, age, etc. When the labor market segmentation is based on discriminatory attitudes, the propagated effects may adversely affect the economic, social and territorial cohesion status of a country. Being in the process of modernizing the labor market, of adapting the economic and social institutions to the requirements of the acquis communautaire, Romania has significant gaps to recover in relation to more developed countries in EU. Although virulent discrimination does not occur on the Romanian labor market, this phenomenon may delay the process of modernization and effective integration in the single European market. In this article, the authors analyze the main forms of discrimination at the regional level based on the following indicators: the Duncan Index at local level; rate discrimination by sex, nationality, and age; wage gap and occupational segregation by gender. They will also assess the effects of various forms of discrimination on the Romanian labor market flexibility.
Keywords: J01; J15; 16; 330; discrimination; wage; labor market